1979
DOI: 10.1073/pnas.76.9.4544
|View full text |Cite
|
Sign up to set email alerts
|

A new glnA-linked regulatory gene for glutamine synthetase in Escherichia coli.

Abstract: Mutations in the ginA region of the Escherichia coli chromosome due to Mu prophage insertion result in two phenotypic classes. One class is G1n and does not synthesize glutamine synthetase IL-glutamate:ammonia ligase (ADPforming), EC 6.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
119
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 13 publications
12
119
0
Order By: Relevance
“…These insertion strains are found in classes 1 and 2 and thus represent at least two different genes and perhaps more. One of these may be gltB, the gene coding for glutamate synthase, since strains with mutations in gltB were originally described as being unable to use L-arginine, proline, or glycine as a nitrogen source (19).…”
Section: Resultsmentioning
confidence: 99%
“…These insertion strains are found in classes 1 and 2 and thus represent at least two different genes and perhaps more. One of these may be gltB, the gene coding for glutamate synthase, since strains with mutations in gltB were originally described as being unable to use L-arginine, proline, or glycine as a nitrogen source (19).…”
Section: Resultsmentioning
confidence: 99%
“…2 shows that the loss of PL drastically lowers the rate of deadenylylation, and somewhat impairs the rate of adenylylation. It has been shown that the product of the glnF gene is required for the synthesis of glutamine synthetase (14,17,18). One model suggests that this product converts the product of another gene, ginG, from a repressor to an activator of glutamine synthetase formation (14,18,19).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the product of the glnF gene is required for the synthesis of glutamine synthetase (14,17,18). One model suggests that this product converts the product of another gene, ginG, from a repressor to an activator of glutamine synthetase formation (14,18,19). The fact that glnF mutants lacking PII due to a mutation in glnB fail to produce glutamine synthetase indicates that the product of the ginG gene, even in the absence of PIIA, is fully capable of repressing glutamine synthetase (14).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial strains and plasmids used in this work are listed in Table 1. Defined W-salts-based media and rich media were as described previously (32). Transformation of CaCl2-treated cells with plasmid DNA and transduction using Plvir were as described previously (23,38).…”
Section: Methodsmentioning
confidence: 99%